ABILITY INTEGRATE DIGITAL TECHNOLOGY BY HEALTH PROFESIONALS DURING THE TEAHING AND LEARNING PROCES IN THE ERA OF GLOBALIZATION: A INTEGRATED RIVIEW - Soares, Domingos; Marni; McKenna, Lissa; Efendi, Ferry; Ahsan; Martin, Nelson; Perreira, Sebastio; Pinto Baptista, Edinha da Silva (LPPM Universitas Duta Bangsa Surakarta, 2023)
In the era of the industrial 4.0, there is an increase in the availability of portable digital technology equipment that supports the learning process in various sectors including health. It is become a core requirement to support the learning process. Digital technology application media such as You Tube, Google Apps, Zoom, Face books, Skype, Dropbox, twitter, WhatsApp and others have become core health learning tools today. The readiness of health workers to utilize digital applications in the learning process, so in needs to be considered. The aims of this study was to explore the readiness of health professional in using digital technology to facilitate the teaching and learning process. Mechanism of goal attainment in this study using the five measures of Whitmore and Knafl. Researcher searched for articles through the google scholar, ProQuest and Science Direct. Article search of January to August 2022 publication period have concentrated of the health professional use technology digital to facelifted their learning. Was used PRISMA checklist with key word: Ability AND health AND Integration AND digital AND Learning. Was choose a cross sectional study for this study. The total 15 articles selected and included in this study with JBI analysis value is at least 88,5%. The use of digital technology in the learning process in the health sector has proven to be very effective and efficient.